Effect of hypothalamic extracts and synthetic LH-RH on proteic synthesis by rat hypothalamus in vitro (Revista Española de Fisiología, 1977)
The incorporation of 14C-Leucine in pituitary proteins in rats, in vitro, has been studied. In absence of stimulation, the pituitaries of adult female rats have shown approximately twice the capacity of protein biosynthesis in vitro than the pituitaries of prepuberal female rats (21 days old). For the stimulation in vitro of the pituitaries, synthetic LH-RH or hypothalamic extracts from adult or prepuberal female rats were used. The pituitaries of adult female rats did not respond to any of the stimulation tests employed. The pituitaries of prepuberal female rats increased their biosynthetic activity significantly, when synthetic LH-RH or adult female rat hypothalamic extract was added to the culture medium. The addition of prepuberal female rat hypothalamic extract did not alter the basic response. The female prepuberal rats injected during 5 consecutive days with FSH and LH, have shown a greater sensibility to LH-RH in vitro than the ones injected with estradiol and progesterone, or with synthetic LH-RH.